Federated States of Micronesia : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
The staff report for the 2008 Article IV Consultation of the Federated States of Micronesia examines economic developments and policies. Growth could recover modestly in the near term as falling commodity prices boost real incomes and progress is made on spending unused compact infrastructure grants. The authorities have limited tools to address risks from the global slowdown. Given the urgency of fiscal consolidation, expenditures should be streamlined and preparations for the comprehensive tax reform intensified.